Anatomy of the Middle Cerebral Artery and some related arteries on 256 MSCT - Tuan Son, Nguyen; Xuan Khoa, Ngo; Quoc Dung, Nguyen; Dinh Thi, Dao (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 35 No 2, 2019)
Abstracts: Introduction: studying the percentage of display and dimensions of the middle cerebral artery and some related arteries on on  256 MSCT data. Methods: A cross-sectional study, with sample size of 261. Results: The percentage of display of middle cerebral artery is 100%; the posterior artery is 76.4; Internal Carotid Artery is 100%. The average diameter, average length are (mm) M1T respectively: 3.25 ± 0.43 and 19.98 ± 6.10; M1 P: 3.26 ± 0.46 and 19.68 ± 6.28; M2T left 2.10 ± 0.48 and 22.85 ± 13.18; M2T right 2.09 ± 0.49 and 23.42 ± 11.89; M2D left 2.48 ± 0.49 and 31.73-16.36; M2D  right 2.55 ± 0.49 and 29.11 ± 15.31. PCoA T 1.29 ± 0.63 and 11.87 ± 4.87; PCoA P 1.26 ± 0.66 and 14.02 ± 9.13; Conclusions: The size of the middle cerebral artery and some related  arteries were accurately evaluated in the study, the image of vascular anatomy was display clearly. Keywords Middle cerebral artery, cerebral angiography, multi-slices computed tomography ... References [1] H.V. Cúc. To the study of arterial blood supply vessels for Vietnamese adults, Ministry of Health research project, Hanoi Medical University, Hanoi, Vietnam (2000) (in Vietnamese). [2] H.M.Tú. To the study of cerebral artery anatomy on MSCT 64 image, Master's thesis in Medicine, Hanoi Medical University, Hanoi, Vietnam (2011) (in Vietnamese). [3] Ogeng'o, J.A. Geometric features of Vertebrobasilar arterial system in adult Black Kenyans, Int. J. Morphol, 36(2) (2018) 544 - 50. [4] KrzyżewsKi, R.M.. Variation of the anterior communicating artery complex and occurrence of anterior communicating artery aneurysm: A2 segment consideration, Folia medica cracoviensia, LIV (1) (2014) 13 - 20. [5] Jiménez-Sosa, M.S. Anatomical variants of Anterior cerebral arterial circle. A study by Multidetector computerized 3D tomographic angiography, Int J. Morphol 35(3) 1121 – 28. [6] Hamidi, C. (2013). Display with 64-detector MDCT angiography of cerebral vascular variations, Surg Radiol Anat 35 (2017) 729 – 36. [7] Dimmick, S.J., et al. Normal variations of the cerebral circulation at multidetector CT angiography, Radiographics 29(4) (2009) 1027 – 43. [8] P.T.Hà. To the study of Willis polygonal anatomy on MSCT 128 image of patients with cerebral aneurysm, Specialish level 2 thesis in Hanoi Medical University, Hanoi, Vietnam. [9] Saha, A. (2013). Variation of posterior communicating artery in human brain: a morphological study, Gomal Journal of Medical Sciences 11(1) (2018). 42 – 6. [10] Gullari, G. K. The branching pattern of the middle cerebral artery: is the intermediate trunk real or not? An anatomical study correlating with simple angiography, J.Neurosurg, 116 (2012) 1024 - 34. [11] Canaz, H., el al Morphometric analysis of the arteries of Willis Polygon, Romanian Neurosurgery, XXXII (1) (2018) 56 - 64. [12] Pedroza, A. (1987). Microanatomy of the Posterior Communicating Artery, Neurosurgery 20(2) (2018) 229 – 35. [13] Keeranghat, P. P., et al. Evaluation of normal variants of circle of Willis at MRI, Int.J. Res Med Sci, 6(5) (2018) 1617 - 22. [14] Tao, X., Yu, et al. Microsurgical anatomy of the anterior communicating artery complex in adult Chinese heads, Surgical Neurology 65 (2006) 155 – 61. [15] Krejza, J., et al. Carotid artery diameter in Men and Women and the relation to body and neck size, Stroke, 37 (2006) 1103 - 5. [16] Masatoukawashima. Microsurgical anatomy of cerebral revascularization. Part I: Anterior circulation, J.Neurosurg, 102 (2005) 116 – 31. [17] Jeyakumar.R., et al, Study of Anatomical Variations in Middle Cerebral Artery, Int.J.Sci Stud 5(12) (2018) 5-10. [18] Brzegowy, P, et al Middle cerebral artery anatomical variations and aneurysms: a retrospective study based on computed tomography angiography findings, Folia Morphol, 77(3) (2018) 434 – 40. [19] Rohan, V., et al, Length of Occlusion predicts recanalization and outcome after intravenous thrombolysis in middle cerebral artery stroke, Stroke, 45 (2014) 2010 - 17. [20] Vijaywargiya, M., et al. Anatomical study of petrous and cavernous parts of internal carotid artery, Anat Cell Biol, 50 (2017) 163 - 70. [21] Bouthillier, et al Segments of the internal carotid artery: a new classification, Neurosurgery, 38(3), (1996) 425 - 32.